The Influence of TikTok-Based Content and Influencer Marketing on Purchase Intention of Eiger Travel Products among Generation Z: The Moderating Role of Gender - Mhd Furqan Akbar; Sabar Sabar; Bambang Widjanarko Otok; Lissa Rosdiana Noer (Journal Research of Social Science, Economics, and Management, 2026)
The rapid growth of short-video–based social media, particularly TikTok, has transformed the way companies engage with consumers and stimulate purchase intention, especially among Generation Z as digital natives. However, for local brands such as Eiger in the travel and outdoor equipment industry, a key challenge remains in converting digital marketing activities into actual purchase intention, as reflected in the gap between high offline conversion rates and relatively low online sales contributions. This research aims to analyze the effects of content marketing and influencer marketing on purchase intention for Eiger’s travel products among Generation Z using a quantitative approach through a survey of 300 respondents who have been exposed to Eiger’s TikTok content. The research model is analyzed using the Stimulus–Organism–Response (S-O-R) framework and tested with Partial Least Squares–Structural Equation Modeling (PLS-SEM) employing SmartPLS software. The findings indicate that both content marketing and influencer marketing significantly enhance perceived enjoyment, which in turn serves as a strong mediator in increasing purchase intention. Furthermore, gender moderates the relationship between content marketing and perceived enjoyment, with female consumers showing greater responsiveness to storytelling and aesthetically appealing content, while male consumers respond more strongly to informative content. In contrast, gender does not moderate the relationship between influencer marketing and perceived enjoyment, suggesting a relatively homogeneous perception of influencers among Generation Z consumers. This study contributes to the literature by extending the application of the S-O-R theory to short-video marketing contexts and enriching empirical insights into Generation Z consumer behavior in Indonesia.